Supporting decision-making in retirement planning: Do diagrams on pension benefit statements help? - Pete Lunn; Féidhlim McGowan (The Economic and Social Research Institute (ESRI), 2018)
This paper investigates whether exposure to explanatory diagrams can affect a major financial decision. In a controlled experiment, participants were given pension benefit statements with or without one or two diagrams, before answering incentivised questions that measured recall, comprehension and choice of contribution rate. The diagrams had at best a marginal influence on recall or comprehension. Nevertheless, a diagram relating contributions to income projections prompted more participants to advocate higher contributions, while both diagrams influenced the rationale participants gave for decisions. The implication is that diagrams may alter pension planning decisions by reinforcing causal inferences, despite the absence of measurable improvements in understanding.
Keywords: C91; D14; D91; 330; information disclosure; retirement planning; decision-making; experiment